Enterocyte-specific FATP4 deficiency elevates blood lipids via a shift from polar to neutral lipids in distal intestine - Seeßle, Jessica; Liebisch, Gerhard; Staffer, Simone; Tuma-Kellner, Sabine; Merle, Uta; Herrmann, Thomas; Chamulitrat, Walee (American journal of physiology. Gastrointestinal and liver physiology, 2024)
Fatty acid transport protein (FATP)4 was thought to mediate intestinal lipid absorption, which was disputed by a study using keratinocyte-Fatp4-rescued Fatp4 -/- mice. These knockouts when fed with a Western diet showed elevated intestinal triglyceride (TG) and fatty acid levels. To investigate a possible role of FATP4 on intestinal lipid processing, ent-Fatp4 (KO) mice were generated by Villin-Cre-specific inactivation of the Fatp4 gene. We aimed to measure circulating and intestinal lipids in control and KO mice after acute or chronic fat intake or during aging. Remarkably, ent-Fatp4 mice displayed an approximately 30% decrease in ileal behenic, lignoceric, and nervonic acids, ceramides containing these FA, as well as, ileal sphingomyelin, phosphatidylcholine, and phosphatidylinositol levels. Such decreases were concomitant with an increase in jejunal cholesterol ester. After a 2-wk recovery from high lipid overload by tyloxapol and oral-lipid treatment, ent-Fatp4 mice showed an increase in plasma TG and chylomicrons. Upon overnight fasting followed by an oral fat meal, ent-Fatp4 mice showed an increase in plasma TG-rich lipoproteins and the particle number of chylomicrons and very low-density lipoproteins. During aging or after feeding with a high-fat high-cholesterol (HFHC) diet, ent-Fatp4 mice showed an increase in plasma TG, fatty acids, glycerol, and lipoproteins as well as intestinal lipids. HFHC-fed KO mice displayed an increase in body weight, the number of lipid droplets with larger sizes in the ileum, concomitant with a decrease in ileal ceramides and phosphatidylcholine. Thus, enterocyte FATP4 deficiency led to a metabolic shift from polar to neutral lipids in distal intestine rendering an increase in plasma lipids and lipoproteins.
Zuerst veröffentlicht: 25. Juni 2024
Gesehen am 20.09.2024